2013
DOI: 10.1371/journal.pone.0062236
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness and Control of Hypertension in Uganda

Abstract: BackgroundPrevention and control of hypertension are critical in reducing morbidity and mortality attributable to cardiovascular diseases. Awareness of hypertension is a pre-condition for control and prevention. This study estimated the proportion of adults who were hypertensive, were aware of their hypertension and those that achieved adequate control.MethodsWe conducted a community based cross sectional survey among people≥15 years in Buikwe and Mukono districts of Uganda. People had their blood pressure mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
123
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(159 citation statements)
references
References 19 publications
(64 reference statements)
24
123
11
1
Order By: Relevance
“…Lastly, a study of adults 65 years of age and older in rural and urban areas of Uganda found that 38.0% of adults were aware of their hypertension [18]. The prevalences of those who were aware of their hypertension and those with controlled hypertension were higher in this study when compared to other studies from sub-Saharan Africa.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 65%
See 3 more Smart Citations
“…Lastly, a study of adults 65 years of age and older in rural and urban areas of Uganda found that 38.0% of adults were aware of their hypertension [18]. The prevalences of those who were aware of their hypertension and those with controlled hypertension were higher in this study when compared to other studies from sub-Saharan Africa.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 65%
“…We found only one study specifically conducted in elderly people over the age of 70, reporting a prevalence of 70% in rural Tanzania [17]. Other studies reported the prevalence of hypertension in people aged 65 and over [7][8][9][10][11][12][13][14][15][16][17][18][19], ranging from 34.5% in urban Kenya [15] to 88.0% in urban Senegal [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,[9][10][11][12][13][14][15] We undertook this study to identify the determinants of raised blood pressure in an exclusively urban population in Kampala, the capital of Uganda.…”
Section: Discussionmentioning
confidence: 99%